INTRODUCTION OF INNOVATION IN THE RESTAURANT BUSINESS - Bobrova, Anna; Špaček, Miroslav, 1954-; Mareš, Jan, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This master’s work is focused on the realization of an innovation in the field of gastronomy. The basis of this work was the introduction of an innovation into a restaurant in Moscow. Aim of this thesis is following: to show the effectiveness of implementation of the innovation into the restaurant using the qualitative survey and financial tools. The main conclusions of this paper are: it is more likely that this is implemented correctly and helped the restaurant to function faster and meet the most important criteria for guests – speed
Vedoucí práce: Miroslav Špaček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses